Dynamics and control analysis during rendezvous in non-Keplerian Earth—Moon orbits - Innocenti, Mario; Bucchioni, Giordana; Franzini, Giovanni; Galullo, Michele; Onofrio, Fabio D’; Cropp, Alexander; Casasco, Massimo (Frontiers in Space Technologies, 2022)
The paper describes the development of a framework capable of addressing some fundamental3 issues in the analysis of proximity operations between two spacecraft that are operating within a4 three-body model defined by two primaries and the spacecraft themselves. The main objective is5 to enable the capability of analysing dynamic and control issues during an automated rendezvous6 between a vehicle and a passive space station orbiting around the Earth - Moon L2 Lagrangian7 point on a near rectilinear halo orbit. The paper presents first a restricted three body model8 dynamics and a nominal approach trajectory, followed by an analysis of the influence of assumed9 actuators and sensors. Critical aspects such as selected failures are investigated, in order to10 ensure passive safety of the mission using impulsive maneuvers. An example of closed loop11 guidance in the near range is also presented and the overall performance are validated with an12 Ephemeris model available in the literature